Chronic exercise interventions for executive function in overweight children: a systematic review and meta-analysis - Lin, Chenxin; Li, Danyi; Wang, Xiaying; Yang, Shuo (Frontiers in Sports and Active Living, 2024)
Objectives To systematically evaluate the effectiveness of chronic exercise in physical activity (PA) as an intervention for executive functions (EFs) in children. Methods We conducted a systematic search in the following online databases: Web of Science, Cochrane Library, PubMed, Embase, and EBSCOhost. The timing is from database inception to July 2023, following PRISMA guidelines. Our inclusion criteria required studies reporting executive function (EF) levels in overweight children (age 0–18 years) before and after interventions. The Cochrane risk of bias tool assessed study bias, and Egger's test examined publication bias. Subgroup analyses considered three moderators: intervention duration, weekly frequency, and session length. Results The meta-analysis included a total of 10 studies with 843 participants. It revealed a statistically significant yet relatively small overall positive effect (g = 0.3, 95% CI 0.16–0.44, P < 0.01) of chronic exercise on EF in overweight children. Importantly, there was no significant heterogeneity (Q = 11.64, df = 12, P = 0.48; I2 = 0). Conclusions Chronic exercise interventions had a consistent positive impact on EF, irrespective of intervention duration, weekly frequency, or session length. However, given limitations in the number and design of studies, further high-quality research is needed to strengthen these conclusions. Systematic Review Registration PROSPERO identifier (CRD42023468588).